Soil Endowments, Female Labor Force Participation and the Demographic Deficit of Women in India - Carranza, Eliana (World Bank, Washington, DC, 2014)
Differences in relative female employment by soil texture are used to explain the heterogeneous deficit of female children across districts within India. Soil texture varies exogenously and determines the depth of land tillage. Deep tillage, possible in loamy but not in clayey soil textures, reduces the demand for labor in agricultural tasks traditionally performed by women. Girls have a lower economic value where female labor opportunities are fewer. Consistently, higher relative female employment in agriculture improves the ratio of female to male children in districts that have a smaller fraction of loamy relative to clayey soils.